If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7y = (-15) 6x + -7y = -15 Solving 6x + -7y = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 6x + -7y + 7y = -15 + 7y Combine like terms: -7y + 7y = 0 6x + 0 = -15 + 7y 6x = -15 + 7y Divide each side by '6'. x = -2.5 + 1.166666667y Simplifying x = -2.5 + 1.166666667y
| 9x-y=81 | | 2(x+5)=-6 | | 2d+5=8d+2 | | 2(x+4)=0 | | j+-1=-2 | | -(5w+u)+3(3u+3w)= | | 4(x-7)=-32 | | ar+2=3R-6t | | 9=0.5*4h+1 | | 2(x+7)=24 | | e+-3=7 | | -6+d=2 | | 2y(x+5)=4w | | 18=-6(p+5) | | -17+c=-13 | | 9=4h+1 | | b+2=-6 | | -5+a=-15 | | 2x-11y=3 | | x+2x+3x+4x+5x=45 | | 3x+5+12=4 | | 2x^2=6x-16 | | x^2=2x+5.5 | | a=2l^2-5l | | 15x-39=27x-74 | | 16x-33=14x-29 | | 16x-33=16x-39 | | 9p-20=-2+6p | | 7.3*3.4= | | 14x+-1=29x+44 | | 9s-9=-6+6s | | 8x+8=9x+4 |